2007
DOI: 10.1186/1471-2407-7-98
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of gemcitabine plus carboplatin in advanced transitional cell carcinoma of the urothelium

Abstract: Background: Recent studies have demonstrated the effectiveness of cisplatin-based combinations in patients with advanced transitional cell carcinoma(TCC) of the urothelium. Concern over cisplatin toxicity instigated a search for alternative regimens. The aim of the study was to evaluate the activity and tolerability of gemcitabine plus carboplatin combination as first-line treatment in patients with advanced transitional cell carcinoma of the urothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Cells (4x10 5 ) were seeded into 6-well culture plates and allowed to grow to ~90-95% confluence in serum-free medium for 48 h. Similar sized wounds were introduced to monolayer cells using a sterile yellow pipette tip, and remove the medium with floating cells carefully. Pre-warmed medium (2 ml) with low dose of epirubicin (2.5 μg/ml) was added.…”
Section: -(45-dimethyl Thiazol-2-yl)-25-diphenyl Tetrazolium Bromimentioning
confidence: 99%
“…Cells (4x10 5 ) were seeded into 6-well culture plates and allowed to grow to ~90-95% confluence in serum-free medium for 48 h. Similar sized wounds were introduced to monolayer cells using a sterile yellow pipette tip, and remove the medium with floating cells carefully. Pre-warmed medium (2 ml) with low dose of epirubicin (2.5 μg/ml) was added.…”
Section: -(45-dimethyl Thiazol-2-yl)-25-diphenyl Tetrazolium Bromimentioning
confidence: 99%
“…There are many reports as to the safety and efficacy of carboplatin-based chemotherapy for metastatic advanced bladder cancer (8,9,17,18). Regrettably, several reports demonstrated that the survival was shorter for CaG than GC.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin is an alkylating anti-cancer agent and less nephrotoxic than cisplatin (7). A carboplatincontaining chemotherapy has been reported to play a potential role in advanced bladder cancer patients with renal impairment (8,9). In a neoadjuvant setting, less toxicity is an important matter, and in particular, the decline in renal dysfunction by chemotherapy affects the perioperative management of cystectomy (10) and may affect postoperative life.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of gemcitabine and carboplatin was developed for patients with metastatic transitional cell carcinoma (TCC) of the bladder unfit for cisplatin-based therapy and subsequently was adopted by additional investigators for such patients (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%